Marketing human resource adaptation through creative promotion and interface design on fintech customer decisions - Didit Darmawan; Rokhmad Thoriqul Hidayat (Jurnal Bisnis Mahasiswa, 2026)
Purpose – This study aims to analyze the influence of online promotional creativity on fintech customer decisions and examine the role of application interface convenience as a reinforcing factor. Design/methodology/approach – The research employs a qualitative literature review with content analysis, drawing on relevant scholarly sources. Findings – Promotional creativity plays a crucial role in attracting attention, building emotional connections, conveying credibility, and shaping perceptions of value among prospective customers. Creative promotions effectively guide potential customers to the threshold of application usage. At this critical juncture, the convenience of the application interface assumes a central role. An intuitive, responsive, and aesthetically pleasing interface validates the promises conveyed through promotion, alleviates user anxiety, and cultivates the trust necessary for final decision-making. These two elements operate synergistically; creativity without convenience results in low conversion rates, while convenience without creativity leads to applications with minimal user adoption. The adaptability of marketing human resources is reflected in their capacity to bridge these two essential dimensions. Research limitations – This study is limited to theoretical literature analysis and does not involve primary empirical data collection; therefore, causal relationships among variables cannot be statistically verified, and the findings have not been tested on a specific population sample. Implications – The practical implications of this study underscore the necessity for close collaboration between marketing teams and product developers, as well as the need to extend marketing success metrics to include post-download stages. Originality – The novelty of this study lies in its integrative synthesis of online promotional creativity and application interface ease as two complementary constructs that jointly shape fintech customer decisions—an interrelationship that has rarely been examined together within the Indonesian digital financial services context.